Indicateurs de gestion et difficultés de renouvellement du « genre professionnel » - Damien Collard; Jean-Baptiste Suquet (Activités)
Based on an intervention research study on the implementation of the RATP “Bus Attitude” project and the consequent evolution of control methods, the article describes and analyses the ticket inspector “job genre”. It shows how certain management indicators can play a critical role in constituting and maintaining the “job genre”, sometimes even devitalizing it. The authors then question the relevance of acting on the management indicators to transform job practices and revitalize the “job genre”. The article highlights the advantages and limitations of such an action and examines the role of the researcher during the intervention.